Demand for dollars: Evidence from survey expectations - Benedikt Ballensiefen; Fabricius Somogyi; Hannah Winterberg (University of Cologne, Centre for Financial Research (CFR), 2026)
We study the determinants of US dollar demand across market participants and traded instruments using survey-based exchange rate and macroeconomic expectations. Leveraging granular FX trading data and forward looking expectations, we present three results. First, currency investors increase their dollar holdings when expecting US dollar appreciation or improved US macroeconomic fundamentals, whereas synthetic dollar funding is driven by forecasted CIP deviations. Second, cross-sectionally, investors rebalance along the factor structure of currency risk into dollars following an expected dollar appreciation. Third, responses to professional forecasts weaken when uncertainty or forecaster disagreement rises, and are lower for forecasters with poorer past accuracy. Our findings demonstrate that long-horizon expectations accurately predict dollar demand across spot, swap, and forward currency markets. We rationalize those finding in a theoretical model of currency demand.
Keywords: F31; G15; F37; 330; Exchange rate expectations; dollar demand; currency flows; FX swaps; survey forecasts